A Review of the Resource Management Task in ATM Networks - Naughton, Shane (Trinity College Dublin, Department of Computer Science, 1995)
[Introduction] An ATM network is a connection-oriented, packet-switched network with the ability to transport heterogeneous services irrespective of characteristics across the same underlying physical network. ATM networks were designed with the extremely high quality and high speeds of existing transmission systems in mind, and the potential future trend in the development of a multitude of services with diverse communication requirements, resulting in a exible and future-safe network. This paper presents a review of the resource management tasks that are necessary to provide network users with their requested performance criteria for the diverse and wide-ranging services they use, while at the same time ensuring there is a sufficiently high and balanced utilisation of the network resources. Section 2 provides an overview of the ATM network and the concepts of virtual connections and virtual paths. Section 3 discusses the need for resource management ofATM networks. Section 4 briefly discusses recommendations in developing resource management techniques. Section 5 considers on-line traffic control mechanisms, Section 6 higher-level network pre-dimensioning mechanismsm, and Section 7 high-level on-line adaptive network dimensioning mechanisms. Finally, Section 6 provides a conclusion.
Keywords: Computer Science